A-weighted sound pressure level calculation in the dissipative atmosphere - BEREZOWSKA-APOLINARSKA, Krystyna; MAKAREWICZ, Rufin (Archives of Acoustics, 1989)
During propagation of sound in the atmosphere a certain fraction of acoustical energy is absorbed by air. Thus, acoustical pressure decreases exponentially with distance. The rate of this drop is expressed by coefficient a which depends on frequency and meteorological conditions. Absorption coefficient α(f) is approximated in this study by binominal function of frequency with two coefficients depending on temperature and relative humidity. The A-weighted sound pressure level is expressed by the function depending on parameters which describe absorption and the distance between the source and the point of observation. Thus the integration is substituted for summation over frequency. bands. Calculations are made and charts are drawn to show differences in A-weighted pressure level calculation which result from α(f) approximation by binominal function.